The Influence of Game-Based Learning on Learning Motivation and Critical Thinking Skills in Elementary Science and Social Studies (IPAS) - Supiyah; Fauzan Adhim; Hariyanto (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of Game-Based Learning (GBL) integrated with pop-up media on students’ learning motivation and critical thinking skills in elementary IPAS learning. This study employed a quantitative approach using a pre-experimental design with a One-Group Pretest–Posttest model. The participants consisted of 19 fifth-grade students selected using a saturated sampling technique. Data were collected using a learning motivation questionnaire and a critical thinking skills test, both of which were validated and tested for reliability. Data analysis was conducted using descriptive statistics, the paired sample t-test, and effect size analysis.The results showed that there was a significant increase in both learning motivation and critical thinking skills after the implementation of Game-Based Learning. The paired sample t-test revealed a significance value of p < 0.001, indicating a statistically significant difference between pretest and posttest scores. Furthermore, the effect size analysis indicated a very high category, demonstrating that the intervention had a strong practical impact. These findings suggest that Game-Based Learning creates an engaging and interactive learning environment that promotes active participation and supports higher-order thinking processes. In conclusion, Game-Based Learning integrated with pop-up media is an effective instructional strategy for improving both learning motivation and critical thinking skills in elementary education. This approach contributes to the development of cognitive and affective competencies aligned with the demands of 21st-century learning.